Identification of widely conserved biosynthetic gene cluster involved in pigment production of Bacillus subtilis - Rune Overlund Stannius; Christopher A. Dunlap; Estelle Morvan; Mélanie Berbon; Sophie Lecomte; Antoine Loquet; Ákos T. Kovács (mSystems)
ABSTRACT Bacillus subtilis is widely studied in the microbial secondary metabolite (SM) field due to its rich variety of important natural products and genetic tractability. We report a pigment observed in B. subtilis soil isolate MB9_B4 on certain media. We characterize the conditions where this pigment is produced and identify the corresponding biosynthetic gene cluster (BGC) using a comparative genomic approach exploiting our strain collection containing other isolates with pigment production ability. The responsible BGC carried several genes, which were annotated as parts of the tryptophan biosynthesis pathway, possibly originating from duplication and divergence of originally primary metabolism. Identification of the pigment gene cluster additionally led to the discovery of additional pigment BGC carrier B. subtilis isolates, some of which were described at the earliest in 1896 under the name Bacillus aterrimus, referring to a characteristic dark pigmentation (the Latin “aterrimus” meaning very black). In addition, we employed solid-state nuclear magnetic resonance and Fourier transform infrared spectroscopies to characterize the chemical groups of the pigment. This study describes the chemical and biological features of a new class of SM BGC, which we hope will serve to improve the current BGC discovery pipelines in Bacilli.IMPORTANCEIdentification of novel microbial secondary metabolites (SMs) and their biosynthetic gene cluster (BGC) has become increasingly difficult, especially in Bacilli, as the tools for screening and genome mining are dependent on clear function or similarity to already known BGCs. Pigments are SMs identified by their absorption of visible light, resulting in a certain color perceived by our eyes at sufficient concentrations. Thereby, pigments provide evidence of a BGC without knowing the sequence or function. Expanding the known repertoire of SM BGCs with novel BGCs will further reinforce the identification of a broader set of BGCs by mining tools such as antiSMASH.